BUDAYA BUGIS DAN PERSEBARANNYA DALAM PERSPEKTIF ANTROPOLOGI BUDAYA - A. B. Takko Bandung Bandung (Fakultas Ilmu Budaya universitas Hasanuddin, 2020)
The Bugis people have specific traditions which they carry as they migrate to different parts of In-donesia. These traditions are believed to be based on ade’ which can be explained as values based on honesty, intellect, propriety, determination, efforts and siri’. When they migrated in the past, they rode all sorts of boats—phinisi being the most well-known.